Distribution And Losses Of Subtermids Anacanthotermes Genus In The Territories Of The Surkhandarya - Abdujalilova Maftuna Isakjonovna (Zien Journals, 2021)
Distribution of termites of the genus Anacanthotermes in residential areas, industrial buildings, fields, hills, mountainous areas in Surkhandarya region, the damage they cause and the development of comprehensive measures to prevent it, study the population ecology, determine their importance in the natural ecosystem is the main goal of our scientific research.
Keywords: Anacanthotermes turkestanicus; historical and cultural monuments; white-headed plant; prevent